Công nghệ tài chính trong thời đại số: Vai trò của kiến thức tài chính - Phùng Thái Minh, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The financial technology (Fintech) industry is growing in Vietnam but little research has been done in this domain. Therefore, based on the Innovation Diffusion Theory and Theory of Planned Behavior, the study examines the relationship between financial literacy and financial technology usage. Based on data on 718 university students and two methods of multivariate regression and structure equation model, the results show that financial knowledge not only directly affects attitude and use of financial technology but also moderates the relationship between technological knowledge and attitude and use of financial technology. Regards to implications for policymakers, more interventions are needed to improve the financial literacy of the Vietnamese people, as financial literacy helps the Fintech industry and the country’s economy to develop sustainably.